Fish growth, yield and economics of conventional feed and weed based polyculture in ponds - Asadujjaman, Md; Hossain, Md. Akhtar (Journal of Fisheries, 2016)
Fish growth, yield and economics of polyculture were evaluated for six months from April to September, 2011 in ponds of Kushtia district, Bangladesh under 4 treatments of feeds and weeds as T0: rice bran, wheat bran and mustard oilcake; T1: Azolla; T2: Grass and T3: Banana leaf. Each treatment had 3 replications. Mean initial stocking weight of fishes like Hypophthalmichthyes molitrix, Catla catla, Labeo rohita, Cirrhinus mrigala, Cyprinus carpio, Ctenopharyngodon idella and Barbonymus gonionotus was 62, 64, 57, 54, 63, 65 and 25 g, respectively. Stocking density (11,115 fishes/ha), liming (250 kg/ha), basal fertilization (Cowdung, 1,500 kg/ha; urea, 60 kg/ha; and Triple Super Phosphate, TSP 60 kg/ha) and periodic fertilization (Urea, 2.5 kg/ha/day; TSP, 2.5 kg/ha/day) were same for all the treatments. Water quality parameters (water temperature, transparency, dissolved oxygen, pH, alkalinity and free carbon dioxide) were monitored fortnightly and fish growth parameters (weight gain and Specific Growth Rate, SGR) were monitored monthly. Treatments did not vary significantly for the mean water quality parameters. Treatment T0 varied more significantly for the mean final weight, weight gain, SGR, survival rate and yield for almost all the species except C. idella and B. gonionotus. Significantly highest CBR was recorded with treatment T1.